2014
DOI: 10.1080/09640568.2014.965299
|View full text |Cite
|
Sign up to set email alerts
|

The impact of domestic energy efficiency retrofit schemes on householder attitudes and behaviours

Abstract: Retrofitting existing housing stock to improve energy efficiency is often required to meet climate mitigation, public health and fuel poverty targets. Increasing uptake and effectiveness of retrofit schemes requires understanding of their impacts on householder attitudes and behaviours. This paper reports results of a survey of 500 Kirklees householders in the UK, where the Kirklees Warm Zone scheme took place. This was a local government led city scale domestic retrofit programme that installed energy efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…This is because the combined impacts of performance gaps and rebound effects are lower than predicted -suggesting in turn that households in middle and upper income areas were already adequately heated and that the insulation added led to reduced energy consumption rather than improved comfort levels. This finding is reinforced by the results of a related survey of the impacts of participation in the scheme that found that thermostat settings in participating households were largely unaffected by KWZ insulation 3 (see Long et al, 2014). Our results therefore offer some evidence to underpin the social case for retrofit based on its expected contribution to tackling fuel poverty.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This is because the combined impacts of performance gaps and rebound effects are lower than predicted -suggesting in turn that households in middle and upper income areas were already adequately heated and that the insulation added led to reduced energy consumption rather than improved comfort levels. This finding is reinforced by the results of a related survey of the impacts of participation in the scheme that found that thermostat settings in participating households were largely unaffected by KWZ insulation 3 (see Long et al, 2014). Our results therefore offer some evidence to underpin the social case for retrofit based on its expected contribution to tackling fuel poverty.…”
Section: Discussionsupporting
confidence: 73%
“…However, the IEA (2013b) and the IPCC (2014) note the significance of multiple barriers that prevent the take-up of energy efficiency measures in buildings. These include lack of awareness and concern, limited access to reliable information from trusted sources, fears about risk, disruption and other 'transaction costs', concerns about upfront costs and inadequate access to suitably priced finance, a lack of confidence in suppliers and technologies and the presence of split incentives between landlords and tenants (IEA, 2013b; IPCC, 2014; Long et al, 2014;Owen et al, 2014). The widespread presence of these barriers led the IEA (2013a) to predict that without a concerted push from policy, two-thirds of the economically viable potential to improve energy efficiency will remain unexploited by 2035.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK policies aiming at improving energy efficiency and reducing C emissions from the domestic sector have undergone significant changes in recent years including programmes that have been run by local authorities and at community levels [6,7]. One of the successful programmes delivered is RE:NEW programme, introduced in 2009 to reduce carbon emissions and energy bills of London's domestic sector [8].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The DECC (2015b) report that approximately 18% of the pre-1919 households live in fuel poverty and may not invest, while Dowson et al (2012) outlined how low affordability is prohibiting low carbon retrofit. Long et al (2015) state that retrofit schemes tend to offer positive results when marketed and hosted correctly. However, there were mixed opinions among HIs on the influence of financial assistance from various sources with tax reduction being the most desired motivation, followed by the government grants.…”
Section: Discussionmentioning
confidence: 99%